Social Exchange: Community Participation and the Future of General Elections in Indonesia - Hikmat Hikmat (Journal of Governance, 2022)
Abstract: In democratic life, community participation plays a critical role. This is because the ultimate goal of a democracy being built is to create direct public participation. One form of democratic development is through elections. To see community participation in general elections, it can be done through social exchanges. Therefore, this study aims to dissect the social exchange theory perspective of people's participation in democratic life through general elections. Studying social exchanges between the community and political elites is fair. It does not violate regulations—descriptive qualitative research method with primary and secondary data retrieval through sources relevant to the research object. Humans are rational beings who always count the sacrifices and rewards of a situation. In any condition, humans will still think about what benefits they get. In the context of democratic life through elections between the public and political elites, it is seen that social exchanges occur between elites who need help (needs votes) and people who look more at economic benefits and psychological comfort. In this study, the author also reveals mutually beneficial relationships between the elite and the community that lead to social exchanges.Keywords: Social Exchange, Community Participation, General Election, Democracy.